Inhibitory test of soursop fruit extract (Annona muricata L) against clinical isolates of Candida albicans from the users of heat polymerized acrylic resin denture : Uji daya hambat ekstrak buah sirsak (Annona muricata l) terhadap isolat klinik Candida albicans dari pengguna gigi tiruan resin akrilik polimerisasi panas - Resa Ferdina; Dina Auliya Amly; Nina Febriani (Makassar Dental Journal PDGI Makassar, 2026)
Health problems that often occur due to the use of dentures are denture stomatitis. Candida albicans is a microorganism in the oral cavity with the highest prevalence in denture stomatitis. One herbal ingredient that can be used as an alternative denture cleaner is soursop fruit (Annona muricata L). This laboratory experimental study used a post-test control group design to provide data on the inhibitory effect of soursop fruit extract on the growth of C.albicans. The samples were C.albicans suspensions obtained from clinical isolates of heat-polymerised acrylic resin (HPAR) denture users, which were given 5 types of treatment with concentrations of 5%, 10%, and 15%, positive control and negative control, with 25 samples. Using SPSS, the data were analysed using the chi-square test. It was concluded that soursop fruit extract had an inhibitory effect on C.albicans clinical isolates from HPAR denture users, with the average inhibitory effect increasing with increasing concentration